PERANAN KREDIT USAHA RAKYAT (KUR) DALAM MENGEMBANGKAN INDUSTRI KECIL MENENGAH (IKM) KOTA TEGAL - Ida Farida; Aryanto Aryanto; Sunandar Sunandar (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Small and medium industries (IKM) play an important role in economic development because the employment rate is relatively high and the capital investment needs are small. Currently improving the performance of small and medium industries (IKM) is still being hit by various obstacles and challenges in the face of competition. Barriers and challenges faced by SME entrepreneurs in improving their business performance are limited capital. The role of banks in economic development is to channel funds for economic activities, one of which is in the form of credit for individual or business entities. Bank Rakyat Indonesia (BRI) has a commitment to help develop Small and Medium Industries (IKM) and improve community welfare.This study aims to determine the role of Business Credit (KUR) in developing Small and Medium Industries (IKM) in Tegal City. This type of research is causative research with survey methods to explain the role of the People's Business Credit (KUR) for the development of Small and Medium Industries. Keywords: People's Business Credit (KUR), Small and Medium Industries (IKM)